Suicidal behaviour in old age - results from the Ibadan study of ageing (2013)
Background: An important reason for the high risk of suicide in the elderly is the determination with which they act out their suicidal thoughts. Early identification of suicidal behaviours in the elderly is therefore important for suicide prevention efforts in this population. Method: Data are from the Ibadan Study of Ageing (ISA), a household multi-stage probability sample of 2149 Yoruba Nigerians aged 65 years or older conducted between 2003 and 2004. We used the third version of the World Health Organization (WHO) Composite International Diagnostic Interview (CIDI) to explore suicidal experiences and behaviours. In this report, only those experiences or behaviours reported to have occurred after the age of 65 years are the focus of analysis. Derived weights were applied to the data in accordance with the study design and associations were explored using logistic regression. The results are presented as odds ratios (ORs) with 95% confidence intervals. Result: In all, 4.0% (95% C.I= 3.1-4.2) of the subjects had suicidal ideation occurring after the age of 65 years, while 0.7% (95% C.I=0.4-1.3) and 0.2% (95% C.I= 0.1-0.4) reported suicidal plans and attempts, respectively. There was a significantly elevated likelihood of suicidal ideation among persons who had experienced spousal separation through death or divorce (O.R=4.9., 95% C.I= 1.5-15) or who were residing in rural settings (O.R=2.5, 95% C.I=1.3-4.8). Conclusion: Suicidal ideation is common among the elderly. About 20% and 6% of those with ideation proceed to plans and attempts, respectively. Circumstances of social isolation and exclusion are important correlates of suicidal behaviour in the elderly.